2022
DOI: 10.1080/14760584.2022.2022478
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events reported after administration of BNT162b2 and mRNA-1273 COVID-19 vaccines among hospital workers: a cross-sectional survey-based study in a Spanish hospital

Abstract: Background The World Health Organization declared COVID-19 a pandemic in March 2020. The first vaccine became available in December, with practically no post-marketing data. Methods An analytical cross-sectional survey-based study was conducted in a third-level hospital in Spain between March and April 2021 to describe the difference in adverse events with the BNT162b2 and mRNA-1273 COVID-19 vaccines. The participants were hospital workers who completed a survey volunta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Among mRNA vaccines, the IR of AE in mRNA1273 was similarly higher than in BNT162b2. The results were supported by the previous research [ 18 , 19 , 20 ]. Since there was still a scarcity of information about the protein subunit vaccine, the current finding provides important reference for the gap.…”
Section: Discussionsupporting
confidence: 91%
“…Among mRNA vaccines, the IR of AE in mRNA1273 was similarly higher than in BNT162b2. The results were supported by the previous research [ 18 , 19 , 20 ]. Since there was still a scarcity of information about the protein subunit vaccine, the current finding provides important reference for the gap.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, data from AE surveillance systems are affected by several biases and cannot quantify the real burden of mild adverse events and those for whom adverse events may be more common. There are several studies to date reporting adverse events from different perspectives or populations, neurological AEs [ 13 ], AEs requiring admissions to EDs [ 14 ], and AEs among HCWs [ 15 , 16 , 17 ]. However, there are few comprehensive population-based reports, especially stratified according to the risk of allergic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…By the end of February 2022, 60% of the world population and 80% of the Taiwanese population has received at least one dose of a COVID-19 vaccine [ 10 , 11 ]. Despite these vaccines showing proven protection against serious illness, hospitalization, and death [ 12 ], some AEs are reported after vaccination [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, only three studies have discussed the potential for urinary-related AEs [ 1 , 5 , 13 ]. However, common AEs following COVID-19 vaccination, namely, sore arm or pain around the injection site and generalized weakness or fatigue, have been widely reported and are carefully monitored [ 1 , 2 , 3 , 4 , 5 ]. Renuka et al investigated the AEs following COVID-19 vaccination using an online questionnaire and reported that the most common urological AE was urinary urgency, with occurrence rates of 0.75% and 1.16% following BNT162b2 mRNA COVID-19 vaccine and COVID-19 mRNA-1273 vaccine, respectively [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation